2009
DOI: 10.1111/j.1740-8261.2009.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF WETNESS LEVEL ON THE SUITABILITY OF WET GAUZE AS A SUBSTITUTE FOR SUPERFLAB® AS A BOLUS MATERIAL FOR USE WITH 6 MV PHOTONS

Abstract: Despite the availability of commercial tissue equivalent bolus material, wet gauze has an application in radiation therapy to provide superior conformance to irregular contours. Wet gauze bolus has the potential to reduce air gaps between the bolus and surface, which could decrease surface dose if sufficiently large to disrupt electronic equilibrium. Wet gauze bolus is often fabricated and wetness judged qualitatively. We assessed the effect of specific gauze wetness levels, quantified in terms of physical den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…and Table ). The authors concluded that while wet gauze is a perfectly acceptable bolus material if carefully constructed and maintained, it should be avoided in the absence of sufficient quality control in order to avoid dosing errors, particularly with low‐energy electron beams …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Table ). The authors concluded that while wet gauze is a perfectly acceptable bolus material if carefully constructed and maintained, it should be avoided in the absence of sufficient quality control in order to avoid dosing errors, particularly with low‐energy electron beams …”
Section: Discussionmentioning
confidence: 99%
“…When wet gauze was used as substitute for SuperFlab with 6 MV photon treatments, dose buildup and absorption were similar at field sizes larger than 7 × 7 cm but at smaller field sizes, wet gauze was less effective as a bolus. Also, the water content of wet gauze needs to be controlled carefully to avoid either inadequate buildup or excessive photon absorption …”
Section: Introductionmentioning
confidence: 99%
“…Despite reports of many researchers who study mainly different treatment techniques and use of various radiation source (photons, electrons and a mixed beam) for this type of tumors, no unified study looking at impact of bolus in achieving an optimal treatment for parotid tumors [15,18,19,21,22,24,27,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The minimum treatment volume includes the ipsilateral parotid bed and the upper neck nodes [8,13]. Using of bolus is other method which is used in radiotherapy of these tumors [14][15][16][17][18]. Bolus is a tissue-equivalent material that is widely used in electron and photon radiation therapy to move or shift the buildup region [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation